Підходи до прогнозування інтегрального індексу стану інвестиційної сфери України - Волощук, Р.В.; Степашко, В.С. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
The purpose of this paper is to investigate approaches to predicting the integral index of the investment needs of Ukraine and their use to support effective management decisions.